2015
DOI: 10.48550/arxiv.1511.08253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Algorithms and Circuits for Scientific Computing

Abstract: Quantum algorithms for scientific computing require modules implementing fundamental functions, such as the square root, the logarithm, and others. We require algorithms that have a well-controlled numerical error, that are uniformly scalable and reversible (unitary), and that can be implemented efficiently. We present quantum algorithms and circuits for computing the square root, the natural logarithm, and arbitrary fractional powers. We provide performance guarantees in terms of their worst-case accuracy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…One can use the circuit to compute the n-bit reciprocal 1/x by setting a = 2 n and b = x in a 2n-bit version of the circuit in order to match the precision of our designs. We also manually created a design following the Newton-Raphson method, which is similar but more accurate to the designs proposed in [12] and [13] and we refer to it as QNEWTON. In contrast to the NEWTON design that follows the standard algorithm, we adjusted the algorithm as follows to reduce the number of lines needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One can use the circuit to compute the n-bit reciprocal 1/x by setting a = 2 n and b = x in a 2n-bit version of the circuit in order to match the precision of our designs. We also manually created a design following the Newton-Raphson method, which is similar but more accurate to the designs proposed in [12] and [13] and we refer to it as QNEWTON. In contrast to the NEWTON design that follows the standard algorithm, we adjusted the algorithm as follows to reduce the number of lines needed.…”
Section: Methodsmentioning
confidence: 99%
“…Most notably, it is essential for quantum linear systems algorithms [10], [11]. Recent work has shown that the space requirements imposed by having to implement the reciprocal reversibly can be prohibitive for implementations on a small quantum computer [12], [13]. The implementation of the reciprocal is used as an example to illustrate the proposed design flows.…”
Section: Introductionmentioning
confidence: 99%
“…If we are interested in properties of g(X), as discussed in the previous section, then, depending on g, we can use basic arithmetic operations to construct the operator G. Numerous quantum algorithms exist for arithmetic operations [19][20][21][22][23] as well as tools to translate classical logic into quantum circuits [24,25]. However, since the latter are not necessarily efficient, the development of new and improved algorithms is ongoing research.…”
Section: Quantum Circuitsmentioning
confidence: 99%
“…Note that these distances are pre-calculated on conventional computers and provided as a matrix to the circuit to decrease the complexity of our circuits. Note that Bhaskar et al [24] have reported the cost of calculating the reciprocals to be O(log 2 (p)) × O(m + p), where m is the total number of qubits dedicated to representing a number (both decimal and integer part) and p is the number of qubits to represent the significant digits after the decimal points. m is discussed in more detail later in this section.…”
Section: A Protein Structures and Energy Tablesmentioning
confidence: 99%